Delivery systems of CRISPR/Cas9-based cancer gene therapy - Biagioni, Alessio (J Biol Eng, 2018)
CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats) is today one of the most reliable method for gene-editing, supporting previous gene therapies technologies such as TALEN, Meganucleases and ZFNs. There is a growing up number of manuscripts reporting several successful gene-edited cancer cell lines, but the real challenge is to translate this technique to the clinical practice. While treatments for diseases based on a single gene mutation is closer, being possible to target and repair the mutant allele in a selective way generating specific guide RNAs (gRNAs), many steps need to be done to apply CRISPR to face cancer. In this review, we want to give a general overview to the recent advancements in the delivery systems of the CRISPR/Cas9 machinery in cancer therapy.